The Role of Air Transport Infrastructure Towards Breaking Seasonality in Emerging Tourism Destinations: A Qualitative Study of Akureyri, North Iceland - Carlos Pastor Chan Santana; Julie Madsen; Saverio Francesco Bertolucci (Island Studies Journal)
This paper examines the impact of air infrastructure development on emerging insular destinations by focusing on Akureyri, located in North Iceland. It examines the intricate relationship between airport infrastructure capacity expansion, the building of human capacity, hospitality infrastructure growth, and seasonality challenges. Through extensive qualitative interviews and literature reviews from stakeholders, policymakers, and academics, the research synthesises how an airport expansion offers democratisation of tourism mobilities and connectedness with the outside world for remotely located communities in the region. The analysis found that despite the stakeholders' increased awareness of the complexities in accommodating year-round tourism, there is a readiness to increase the tourism enterprise flows. Nevertheless, the study shows a high deficit in hospitality infrastructure along with regional investment imbalances, revealing the lack of a comprehensive capacity building strategy. Ultimately, the authors advocate for an 'extended capacity' approach to tackle the challenges presented in the process of overcoming seasonality issues. The paper stresses the need for developed human skill capacity and diversified services and products alongside infrastructure capacity upgrades. The gained insights are gathered in two figures. The first identifies and maps the contextual landscape encompassing North Iceland's tourism industry and its stakeholders, while the other showcases the complexity of the process the destination undergoes for breaking seasonality, while exposing the interconnections of potential outcomes, stakeholders' needs, and the existing and in process capacities.